Guest Editor's IntroductionThe Mimetic Condition: Theory and Concepts. Issue 1 (April 2022) - Lawtoo, Nidesh
Abstract : This introductory essay articulates some of the theoretical and conceptual foundations internal to the post-literary mimetic turn. Drawing on an ERC-funded transdisciplinary project titled Homo Mimeticus, out of which this special issue on The Mimetic Condition emerged, the introduction furthers Gunther Gebauer and Christoph Wulf's account of mimesis as a 'human condition' in order to propose a new theory of homo mimeticus for the post-literary age. This entails a paradigm shift from dominant translations of mimesis as realistic representation toward an embodied, immanent, and relational conception of subjectivity. This mimetic subject is neither limited by the sameness of mimetic desire nor by the difference of the linguistic sign dominant in the twentieth century but, rather, is attentive to both the pathological and patho- logical re -turns to homo mimeticus in the twenty-first century. The concepts of 'mimetic pathos', 'pathos of distance', the 'mimetic unconscious', and hypermimesis provide theoretical steps for rethinking the mimetic condition in the age of hypermimetic reproductions.